Apoptotic effect on HeLa Cells produced by Chlamydia trachomatis-LPS - Beatriz Millán-Mendoza (Kasmera, 2007)
The interaction between the lipopolysaccharide (LPS) of Chlamydia trachomatis and mammalian cells is still largely unknown. Chlamydia trachomatis is an obligate intracellular bacterium responsible for several diseases in humans and animals. In this work, thanks to the isolation of the lipopolysaccharide from two serovars of Chlamydia trachomatis (LGV1-LGV2) and using a nuclear supravital fluorescent stain (Hoechst 33258), it was possible to investigate the apoptotic effect on HeLa cells. This work shows the apoptotic effect on HeLa cells when they were exposed to C. trachomatis-LPS from two serovars at concentrations equal to or higher than 0.5 µg/mL for a period of 48h. and also the lack of cellular response in the absence of C. trachomatis-LPS or in the presence of LPS obtained from other bacteria. Additionally, the use in equal conditions of polymyxin B, known as an inhibitor of bacterial LPS, showed a decrease of the apoptotic effect in such cells indicating that the cellular response observed was produced by C. trachomatis-LPS. These results support the theory that the LPS from C. trachomatis could be responsible for the toxic effect on cervical cells infected by these bacteria.